5-caffeoylquinic acid retention in spray drying of cocona, an Amazonian fruit, using hydrolyzed collagen and maltodextrin as encapsulating agents. Issue 12 (8th September 2021) - Vargas-Muñoz, Diana Patricia; Cardoso da Silva, Leticia; Neves de Oliveira, Luiza Andreza; Teixeira Godoy, Helena; Kurozawa, Louise Emy
Abstract: Cocona is native to Amazon, rich in 5-caffeoylquinic acid (5-CQA). The objective of this study was to evaluate the influence of the inlet air temperature (120-180 °C) and of the combination of encapsulating agents maltodextrin and hydrolyzed collagen (MD:HC, 0:100-100:0), on cocona powders, by central composite rotatable design (CCRD). The main results were: solids recovery of 30.9-68.2%, antioxidant capacities of 98.6-141.3 mM TE/g (FRAP) and 53.1-143.3 mM TE/g (ABTS), 5-CQA of 99.7-670.8 µg/g and encapsulation efficiency of 91.2-98.1%. The best parameters, by CCRD were an MD:HC of 20:80 and a temperature of 120 °C, with high values of FRAP (88.12 mM TE/g), ABTS (81.39 mM TE/g), 5-CQA (532.20 µg/g), and encapsulation efficiency (95.97%). Additionally, cocona powder was evaluated for hygroscopicity (17.14 g/100 g), solubility (76.51%), morphology and color. It is, therefore, a good alternative to enhancing foods, given the bioactive properties of the fruit and of HC.